Design, implementation, and evaluation of an evaporative cooling system for dairy cows in a commercial farm - Baradín-Sandí, Francisco (2026)
Introduction. Heat stress in dairy cattle is a growing problem, especially in tropical climates like in Costa Rica. This phenomenon negatively impacts milk production, animal health, and reproductive efficiency. Therefore, it is crucial to implement mitigation strategies that improve cattle welfare and farm profitability. Objective. To evaluate the effects of an evaporative cooling system (ECS) on the welfare, productivity, and reproductive performance of Jersey cows. Materials and methods. Over a three-month period during the dry season, the herd was divided into two homogeneous blocks: one exposed to the ECS and the other serving as a control. Variables such as temperature, humidity, surface body temperature, milk yield and composition, reproductive performance, and somatic cell count were measured. Additionally, a financial analysis was conducted to assess the economic feasibility of the system. Results. The results showed a significant reduction in the Temperature-Humidity Index (THI) in the area under the ECS, with an average decrease of 2.91 points, and a drop of up to 3.97 °C in surface body temperature of exposed cows. However, no significant improvements were observed in milk production or reproductive parameters. Somatic cell counts also did not increase. From a financial perspective, the investment was not profitable under the current conditions. Conclusion. The evaporative cooling system significantly reduced the surface temperature of cows without negatively affecting udder health, but it did not improve milk production or reproductive indicators under the environmental conditions of the study.